Droga, podróż, wędrówka w Tylko kochankowie przeżyją Jima Jarmuscha - Grabias, Magdalena (Humaniora. Czasopismo Internetowe, 2020)
Two first decades of the 21st century have revealed an increasing popularity of the horror genre. In particular, we have been witnessing the renaissance of Gothic cinema, especially the vampire sub-genre. It is conspicuous that the original vampire story formula has lately undergone numerous significant alterations. Vampires have evolved from cold and soulless monsters to humanised romantic heroes. In the new millennium, a static Gothic diegesis gets frequently replaced by a dynamic reality, in which movement is a predominant feature. This article is devoted to the motifs of the road, journey and travels in Jim Jarmusch’ film Only Lovers Left Alive.